Phenotyping of a M. maximus founder population for breeding purposes for its BNI potential, biomass production, forage quality and nitrous oxide emissions - Villegas, Daniel Mauricio; Arévalo, Ashly; Nuñez, Jonathan; Mazabel, Johanna; Arango, Jacobo (2019)
Modern agricultural systems in the tropics are characterized by low resource use efficiency, low productivity and demand large extensions of land. To tackle this scenario, improved pastures have enormous potential to contribute towards a sustainable livestock model, of high productivity and environmental services provision. Guineagrass (Megathyrsus maximus) is a widely diverse tropical pasture, recognized for its high biomass production, nutrition quality and relatively simple manage under grazing.